Minimizing blood loss and transfusion rate in laparoscopic liver surgery: a review - Wojciech Serednicki; Wacław Hołówko; Piotr Major; Piotr Małczak; Michał Pędziwiatr (Videosurgery and Other Miniinvasive Techniques)
Laparoscopic liver resection has become a standard practice in many surgical wards in elective liver surgery, due to its positive impact on reducing hospital stay and postoperative complications, including lower blood loss and transfusion rate. However, achieving proper hemostasis in liver surgery, due to its vast blood supply, still remains a main concern to surgeons. Therefore, numerous techniques were and are still being developed to further reduce blood loss and transfusion rate. The aim of this literature review was to summarize the best available methods for achieving the minimal blood loss and transfusion rate in laparoscopic liver surgery, according to the newest data.